The Influence of Self-control and Peer Conformity on the Consumptive Behavior of E-commerce User Students at the Faculty of Economics UNIMED - Manihuruk, Frido Evindey; Siregar, Filja Azkiah; Marbun, Jonatan; Hidayat, Nasrullah (Jurnal Penelitian Ilmu Sosial dan Eksakta, 2024)
The consumptive behavior of e-commerce users among students has become a complex issue within the UNIMED economics faculty campus environment. Environmental influences such as peer pressure are believed to be one of the drivers behind individuals purchasing products on e-commerce platforms. Self-control in excessive consumption is a crucial factor in reducing uncontrolled consumptive behavior. This research aims to analyze the influence of self-control and peer conformity on the consumptive behavior of e-commerce users among students in the UNIMED economics faculty environment. This quantitative study utilizes primary data obtained from a population of 3,345, with 100 respondents as its sample. Data collection is conducted using questionnaires containing 15 items for each variable. The results of this study indicate that self-control has a non-significant negative influence on students' consumptive behavior. Meanwhile, peer conformity has a significant positive influence on students' consumptive behavior. These findings demonstrate that students in the UNIMED economics faculty lack self-control and prioritize peer decisions, resulting in increased consumptive behavior. This research is expected to highlight the importance of enhancing self-control and raising students' awareness of peer influence in consumption decisions